Composit firm electrolits on the basis of kalium sulphate and their application - Halenov, O.S.; Kolesnikov, V.A.; Kasymov, S.S.; Bajsagov, J.Z.; Jurov, V.M. (Recent Contributions to Physics, 2012)
In work methods of synthesis of firm electrolits on the basis of kalium sulphate are considered. Their electrophysical characteristics and influence on ionic conductivity of humidity and presence of various gases are described. On the basis of the found out laws pre-production models of devices for measurement of humidity of grain and the analysis of harmful gases are developed and made.